O debate da Escola de Frankfurt e suas contribuições para uma reflexão crítica da sociedade contemporânea - Rodrigo Marques Leistner (Ciências Sociais Unisinos)
This work brings back the endogenous debate established among some thinkers of the Frankfurt School, especially when it comes to the different theoretical perspectives on the relations between social action and structure, as well as the distinct perceptions about the rationalities (practical or communicative) that organize the connection between individuals and society. It aims to verify the way that the authors related to the critical theory understood the relations between subjective and structural spheres in terms of the possibilities of social emancipation and exercise of deliberative practices. In this perspective, it considers a theoretical division established inside the school itself, whose expression occurs since the epistemological differences existing between the central nucleus of the thinking of the school and a host of peripheral authors. The works produced by this “marginal” nucleus, as well as its posterior refinement in the work of Habermas, present theoretical alternatives of relational features which oppose to the structural and skeptic vision existent in the works of Horkheimer, Adorno and Marcuse. It is precisely in the recovery of these endogenous frontiers that it is intended to ponder the possible contributions of the Frankfurtian thinking for a critical perspective of the contemporary society.